China in the Era of Xi Jinping : Domestic and Foreign Policy Challenges - Bekkevold, Jo Inge; Ross, Robert S., 1954- (Book collections on Project MUSE., 2016)
Xi Jinping became general secretary of the Communist Party of China in 2013, taking his leadership role at a time of continuing economic expansion and military modernization that seem destined to make China a superpower. Xi has become China's most powerful and popular leader since Mao, and his vision of the "Chinese dream" of "great renewal" does not seem like an empty political slogan. But the image of China's meteoric rise masks some problems that are simmering both at home and abroad. This book will examine the prospects for China's continuing rise but also the emergent and unintended consequences posed by China's domestic transformation and international assertiveness. The three most urgent and interrelated domestic challenges facing China's leaders are sustaining economic growth, fighting corruption, and maintaining social stability. In foreign policy, its neighbors and the United States have questions about what China wants and whether it will be a revisionist state or be content with most aspects of the status quo. There is also concern that nationalist pressures within China may put domestic pressure on foreign policy.